Innovation In Processing Local Food Products for Students of The Tourism Marketing Management Study Program at The Indonesian University of Education - Iskandar, Antonius; Rabasari, Sara; Sugiarto, Yayan; Aditya Wahyono, Surya; Kuntala Devi, Ghini (Inaba of Community Services Journal, 2023)
Development of food innovations that use local raw materials as the main ingredient. This includes organic foods and food products that support local farmers. Traditional Indonesian food products such as rendang, chili sauce and crackers have undergone innovation in a more modern and ready-to-eat form for the global market. One of the innovations in processed local food products is cassava, cassava, or cassava in English, which is an important root crop in Indonesia. food consumption in many countries around the world. Innovation in the processing and use of cassava has played a major role in increasing food production and added value. Modernization in the processing and processing of cassava products in local food is an effort to create products that are more diverse, of higher quality, and in line with current consumer trends. This modernization can provide added value to processed cassava products and help promote the use of cassava in various dishes, one of which can be applied in cassava Bomb Brulle cheese sauce, Desert coconut snowballs. The collaboration between the NHI Tourism Academy (AKPAR) and students from the Indonesian University of Education (UPI) to organize training is a positive step in improving the skills and knowledge of UPI students, especially in the tourism marketing department, to equip graduates to open entrepreneurship. Consider establishing long-term cooperation between Akpar NHI and UPI. This could include regular training, student exchanges, or other joint projects that are beneficial to both parties.